2007
DOI: 10.1186/1472-6831-7-9
|View full text |Cite
|
Sign up to set email alerts
|

Perceived dental treatment need among older Tanzanian adults – a cross-sectional study

Abstract: BackgroundNeed perceptions for dental care play a key role as to whether people in general will seek dental care. The aim was to assess the prevalence of perceived need of problem based dental care, dental check-ups and any type of dental care. Guided by the conceptual model of Wilson and Cleary, the relationship of perceived need for dental care with socio-demographic characteristics, clinically defined dental problems and self-reported oral health outcomes was investigated. Partial prosthetic treatment need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
(52 reference statements)
3
17
0
Order By: Relevance
“…Consistent with theory and empirical findings, impaired OHRQoL was positively associated with perceived need for dental care in Kilwa students, indicating that a full understanding of young people's need for dental care cannot be captured by clinical indicators alone. These findings are consistent with previous reports, suggesting that self-evaluations of oral health status rather than disease presence per se are the primary determinants of perceived dental treatment needs [ 13 , 38 , 39 ]. Consistent with results of previous studies in older age groups, the present findings suggest that normatively assessed and perceived need for dental care differs among Tanzanian primary schoolchildren [ 38 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with theory and empirical findings, impaired OHRQoL was positively associated with perceived need for dental care in Kilwa students, indicating that a full understanding of young people's need for dental care cannot be captured by clinical indicators alone. These findings are consistent with previous reports, suggesting that self-evaluations of oral health status rather than disease presence per se are the primary determinants of perceived dental treatment needs [ 13 , 38 , 39 ]. Consistent with results of previous studies in older age groups, the present findings suggest that normatively assessed and perceived need for dental care differs among Tanzanian primary schoolchildren [ 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with previous reports, suggesting that self-evaluations of oral health status rather than disease presence per se are the primary determinants of perceived dental treatment needs [ 13 , 38 , 39 ]. Consistent with results of previous studies in older age groups, the present findings suggest that normatively assessed and perceived need for dental care differs among Tanzanian primary schoolchildren [ 38 ]. The present results provide insight into what oral impacts guide Kilwa students' perceived need for dental care.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the model performed equally well in both study populations, explaining almost the same amount of variation in oral health satisfaction. In accordance with other studies [23,27], oral health indicators at the various levels of the conceptual hierarchy influenced the overall responses to oral health status positively and significantly, but differently.…”
Section: Discussionsupporting
confidence: 91%
“…A study conducted in coast region in Tanzania revealed that about half of the elderly had a problem oriented care. [22] The most common oral care carried out in public dental clinics is tooth extractions. [23][24][25] Additionally, the limited number of dental clinics that offer restorative care in Tanzania has been as an obstacle towards accessing restorative services when needed.…”
Section: Dental Care In Tanzaniamentioning
confidence: 99%